The legal Quagmires in the Anti-Money Laundering And Anti-Terrorism Financing Act 2001 / Zaiton Hamin ... [et al.] - Hamin, Zaiton; Abdul Razak, Muhammad Umar; Wan Rosli, Wan Rosalili (2014)
Money laundering is considered as a significant worldwide phenomenon, with grave economic, political and social ramifications. Widespread international concerns over such crime have led to the establishment of international policies and standards by the Financial Action Task Force (FATF) aimed at preventing it, and ultimately criminalizing it within the national boundary. In accordance with such policies, Malaysia introduced the Anti-Money Laundering Act in 2001(AMLA) as a legal modality in governing such crime. It was amended and renamed to AMLATFA in 2003 to include terrorism financing. However, of late concerns have been voiced relating to some of its instrumental flaws including the exclusion of certain offences from the predicate offence list and the comparatively low sanctions for money laundering. Such deficiencies would inevitably raise the question of the utility of AMLATFA in curbing money laundering and terrorism financing in the country. Within this uncertain legal landscape, this paper will highlight the conundrums surrounding the said legislation. The authors contend that despite the adherence to global governance standards, legal deficiencies in the AML/CFT regime in Malaysia remained, and that such a problem merit urgent attention and action from the relevant authorities. This paper employs a doctrinal legal research and secondary data of which the AMLATFA is the primary source. The secondary sources for this article include decided cases, articles in academic journals, books and online databases.